1977
DOI: 10.1063/1.89723
|View full text |Cite
|
Sign up to set email alerts
|

Optical phase conjugation in a lithium formate crystal

Abstract: Optical phase reversal has been demonstrated using type-II phase matching in lithium formate operated as a degenerate optical parametric amplifier with pump peak powers as low as 103 W. The amplifier was driven in a collimated geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Phase conjugation using a three-wave mixing interaction in a nonlinear crystal has been reported by Avizonis et al 159 Heer and G r i f f e n 1 42 have generated a forward conjugate wave in thin nonlinear optical media using the D F W M geometry shown in Fig. Numerous authors have reported phase conjugation using various forms of stimulated scattering, including stimulated B r i l l o u i n , 1 4 9 -1 5 5 R a m a n , 1 5 6 , 1 5 7 and R a y l e i g h 1 58 scattering.…”
Section: O S C I L L a T O R O U T P U T F I L M P L A N E -mentioning
confidence: 80%
“…Phase conjugation using a three-wave mixing interaction in a nonlinear crystal has been reported by Avizonis et al 159 Heer and G r i f f e n 1 42 have generated a forward conjugate wave in thin nonlinear optical media using the D F W M geometry shown in Fig. Numerous authors have reported phase conjugation using various forms of stimulated scattering, including stimulated B r i l l o u i n , 1 4 9 -1 5 5 R a m a n , 1 5 6 , 1 5 7 and R a y l e i g h 1 58 scattering.…”
Section: O S C I L L a T O R O U T P U T F I L M P L A N E -mentioning
confidence: 80%
“…4-7, with transversal dimensions that almost perfectly match those of the real objects down to 40 m. As a final remark, we note that the results for case (b) are better in quality than those for case (a), because the holographic image is real and hence there is no need for any optical element to image it. Scheme (b) is thus more suitable for applications, among which we mention optical phase conjugation, 10,19,24,25 that can be used for recovering wave fronts from aberrations. 20,26,27 Fig .…”
Section: Discussionmentioning
confidence: 99%
“…3) x F /z F Ӎ sin ␤ 1 and y F /z F Ӎ sin 1 . By introducing, in expressions (19), the phasematching conditions that apply to the present case ( 3 ϭ 0), i.e., k 1 sin 1 ϭ Ϫk 2 sin 2 and (20) where we have defined…”
Section: Application Of Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Another potentially useful property is that, when wavelength-converting, the idler beam image is the phase conjugate of the input beam, and, with OPA, the phase conjugation occurs in the forward direction. As a result, OPA imaging can be performed without the use of imaging lenses [10][11][12][13] ; if the same wavelength is used for the signal and the idler (that is, operating at degeneracy), an exact replica of the spatial distribution of the input signal, but with gain, appears the same distance after the nonlinear medium as the object before it. A typical OPA imaging apparatus.…”
Section: Optical-parametric-amplification Imagingmentioning
confidence: 99%